2022
DOI: 10.3390/ijerph19137851
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Environmental Information Disclosure on Rural Residents’ Pro-Environmental Behavior

Abstract: Rural residents’ pro-environmental behavior plays a critical role in rural environmental governance. This paper examines how the perception of government environmental information disclosure (EID) can promote rural residents’ pro-environmental behavior (PEB) using a questionnaire survey. Using Zhejiang province of China as a case study, we designed a four-stage mixed sampling method, which yielded 783 valid responses. We used ordinary least squares (OLS), an ordinal logit model and a mediation effect model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The more the consumer is provided with pro-sustainable information in their consumption decision, the more effective their sustainable behaviors will be and the less uncertainty there will be in deciding on their environmental practices (Díaz et al, 2020;Xu et al, 2023). Pro-sustainable information boosts resource conservation efforts and their efficient use (Yang et al, 2022) the search for more information of this type motivates consumers to adopt circular consumption behaviors. Finally, the positive relationship between pro-sustainable information research and circular consumption, when mediated by circular habits, provides us with new knowledge.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The more the consumer is provided with pro-sustainable information in their consumption decision, the more effective their sustainable behaviors will be and the less uncertainty there will be in deciding on their environmental practices (Díaz et al, 2020;Xu et al, 2023). Pro-sustainable information boosts resource conservation efforts and their efficient use (Yang et al, 2022) the search for more information of this type motivates consumers to adopt circular consumption behaviors. Finally, the positive relationship between pro-sustainable information research and circular consumption, when mediated by circular habits, provides us with new knowledge.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The more the consumer is provided with pro‐sustainable information in their consumption decision, the more effective their sustainable behaviors will be and the less uncertainty there will be in deciding on their environmental practices (Díaz et al, 2020; Xu et al, 2023). Pro‐sustainable information boosts resource conservation efforts and their efficient use (Yang et al, 2022), positively influencing circular habits. Furthermore, the positive relationship between pro‐sustainable information research and circular consumption found in this study corroborates the conclusions of several studies (Calvo‐Porral & Lévy‐Mangin, 2020; Pinho, & Gomes, 2023; Stangherlin et al, 2023) demonstrating that the search for more information of this type motivates consumers to adopt circular consumption behaviors.…”
Section: Discussion Of Results and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different types of environmental regulations solve environmental pollution problems in different ways. Many studies show that environmental regulation can significantly reduce PM2.5 emissions, CO 2 emissions, and SO 2 emissions ( 25 , 53 55 ), which also impacts residents' environmental protection behavior ( 56 ) and environmental responsibility ( 57 ). At the same time, environmental regulation can improve the green production efficiency and green investment of enterprises ( 58 ).…”
Section: Policy Background and Literature Reviewmentioning
confidence: 99%